Biphasic Regulation of Caveolin-1 Gene Expression by Fluoxetine in Astrocytes: Opposite Effects of PI3K/AKT and MAPK/ERK Signaling Pathways on c-fos - Li, Baoman; Jia, Shu; Yue, Tingting; Yang, Li; Huang, Chen; Verkhratsky, Alexej; Peng, Liang (Frontiers in Cellular Neuroscience, 2017)
Previously, we reported that fluoxetine acts on 5-HT2B receptor and induces EGF receptor transactivation in astrocytes. Recently, we have found that chronic treatment with fluoxetine regulates Cav-1/PTEN/PI3K/AKT/GSK-3β signalling pathway and glycogen content in primary cultures of astrocytes with bi-phasic concentration dependence. At low concentrations fluoxetine down-regulates Cav-1 gene expression, decreases membrane content of PTEN, increases PI3K activity, and increases phosphorylation of GSK-3β and increases its activity; at high concentrations fluoxetine acts on PTEN/PI3K/AKT/ GSK-3β in an inverse fashion. Here, we present the data indicating that acute treatment with fluoxetine at lower concentrations down-regulates c-Fos gene expression via PI3K/AKT signalling pathway; in contrast at higher concentrations fluoxetine up-regulates c-Fos gene expression via MAPK/ERK signalling pathway. However, acute treatment with fluoxetine has no effect on Cav-1 protein content. Similarly, chronic effects of fluoxetine on Cav-1 gene expression are suppressed by inhibitor of PI3K at lower concentrations, but by inhibitor of MAPK at higher concentrations, indicating that the mechanism underlying bi-phasic regulation of Cav-1 gene expression by fluoxetine is opposing effects of PI3K/AKT and MAPK/ERK signal pathways on c-Fos gene expression. The effects of fluoxetine on Cav-1 gene expression at both lower and higher concentrations are abolished by AG1478, an inhibitor of EGF receptor, indicating the involvement of 5-HT2B receptor induced EGF receptor transactivation as we reported previously. However, PP1, an inhibitor of Src only abolished the effect by lower concentrations, suggesting the relevance of Src with PI3K/AKT signal pathway during activation of EGF receptor.